Information and multiaccess interference in a complexity-constrained vector channel - Müller, Ralf; et al. (Journal of Physics A: Mathematical and Theoretical, 2007)
A noisy vector channel operating under a strict complexity constraint at the receiver is introduced. According to this constraint, detected bits, obtained by performing hard decisions directly on the channel's matched filter output, must be the same as the transmitted binary inputs. An asymptotic analysis is carried out using mathematical tools imported from the study of neural networks, and it is shown that, under a bounded noise assumption, such complexity-constrained channel exhibits a non-trivial Shannon-theoretic capacity. It is found that performance relies on rigorous interference-based multiuser cooperation at the transmitter and that this cooperation is best served when all transmitters use the same amplitude. © 2007 IOP Publishing Ltd.